Evolution of Mixed Connective Tissue Disease in 7 Years Old Child: Clinical Case - Tamara P. Makarova; Khakim M. Vakhitov; Dina R. Sabirova; Dinara I. Sadykova; Liliya R. Khusnutdinova; Natalya N. Firsova; Anna A. Kucheryavaya (Вопросы современной педиатрии)
Background. Mixed connective tissue disease (Sharp syndrome) is the rare chronic autoimmune pathology combining various features of systemic lupus erythematosus, systemic scleroderma, rheumatoid arthritis, dermatomyositis and high antibody titer to nuclear ribonucleoprotein. The mixed connective tissue disease may evolve into other systemic diseases over time. Description of any cases of mixed connective tissue disease and its evolution in Russian patients has not been published previously.Clinical Case Description. The results of observations of the child with clinical and immunological signs of the mixed connective tissue disease followed by the progression of systemic scleroderma symptoms and development of Sjogren's syndrome in the short period of time are presented in the article. Improvement (such as pain attenuation, increase in volume of movements in affected joints, decrease of Raynaud syndrome manifestations duration) was observed on treatment (methotrexate 10 mg/week with subsequent addition of prednisolone 0.75 mg/kg/day).Conclusion. Timely diagnostics of clinical signs of the systemic diseases debut is crucial for correct patient routing and for achieving of disease improvement.